Imitation of human muscle by using an electromechanical system - Unal, Engin; Ozcan, Samet (Walter de Gruyter Gmbh, 2022)
Humanity is increasingly approaching the dream of making humanoid robots that have been imaginary for many years with advancing technology. Designs that are close to perfect in humanoid or animal-like robots emerge with the research and development studies carried out by researchers on this subject. In order to develop these robots, the movement mechanism of humans and animals must be examined again. Robots will work in place of people and can be used in wars with the development of these systems. In this study, the usability and performance of the linear actuator, which is widely used in various mechatronic systems as a linear motion provider, in the artificial muscle mechanism have been tested. Moreover, it tried to create a similar prototype by examining the working logic of skeletal muscle. The different aspect of the study is to indicate how the motion energy can be gained without using the conventional motors that are used in robot technologies. The artificial musculature is formed by arranging the electromagnets in a row, leaving a gap between them. The desired length of movement is formed as a result of the activated electromagnets gaining magnetism and closing the gap. In the study, the maximum load that the artificial muscle can pull according to the given voltage was 130.18 N and the average maximum gap length of each sarcomere was 1.68 mm. The efficiency of artificial muscle was found to be 56% compared to human muscle.
Keywords: artificial muscle; electromagnet; muscle fiber; robotic; sarcomere